Urgensi Perlindungan Lahan Pertanian Pangan Terhadap Alih Fungsi Lahan di Daerah Istimewa Yogyakarta - Gunawan Wibisono; Yeni Widowaty (KRTHA BHAYANGKARA, 2023)
One of the threats to achieving food security and sovereignty is the conversion of agricultural land functions because its application has an impact on food production, the physical environment, and the level of welfare of rural farmers whose livelihoods depend on their land which causes a decline in farmers' welfare. The conversion of agricultural land functions is also the cause of the limited area of cultivated land. Land conversion activities in the Special Region of Yogyakarta are increasing every year due to economic factors and population growth rates. The purpose of this study is to examine the urgency of protecting food agricultural land against land conversion in the Special Region of Yogyakarta and to propose future concepts related to the problems of existing land function specialists, especially in the Special Region of Yogyakarta. The research method is normative research and empirical research with primary, secondary and tertiary legal materials. The technique of taking legal materials in this study uses library research. Results and Conclusions: The form of expert protection for food agriculture land functions in the Special Region of Yogyakarta is regulated in "Regional Regulation of the Special Region of Yogyakarta Number 6 of 2021 concerning Amendments to Regional Regulations of the Special Region of Yogyakarta Province Number 10 of 2011 concerning Protection of Sustainable Food Agricultural Land. The Regional Regulation more or less contains: Determination of land that can be used as land for food agriculture, Mechanisms related to protection plans, Determination of the area of food agriculture land, Prohibition on converting food agricultural land Government efforts (By providing incentives for people whose land is on food agricultural land), Provisions violation of the prohibition of land function experts, and so on. The future concept concerns efforts to reduce the activities of land function experts that occur including so that no land function experts should minimize the chances of their occurrence by reducing the driving factors for these occurrences, controlling the activities of land function experts to reduce potential impacts that will arise and neutralize or overcome negative impacts